Recurrent opportunistic infections in a HIV-negative patient with combined C6 and NFKB1 mutations: A case report, pedigree analysis, and literature review - Zheng Yamei; Guan Liwen; Li Jiao; Fu Yihui (Open Medicine)
Recurrent opportunistic infections are particularly common in patients infected with human immunodeficiency virus (HIV). However, these opportunistic infections have also been reported in HIV-negative patients, especially those with primary immunodeficiency disorder (PID), a condition that involves a large heterogeneous group of disorders arising from defects in immune system development and/or function.